Scalable spatio-temporal Bayesian analysis of high-dimensional electroencephalography data - MOHAMMED, Shariq; DEY, Dipak K. (Canadian journal of statistics, 2021)
We present a scalable Bayesian modelling approach for identifying brain regions that respond to a certain stimulus and use them to classify subjects. More specifically, we deal with multi-subject electroencephalography (EEG) data with a binary response distinguishing between alcoholic and control groups. The covariates are matrix-variate with measurements taken from each subject at different locations across multiple time points. EEG data have a complex structure with both spatial and temporal attributes. We use a divide-and-conquer strategy and build separate local models, that is, one model at each time point. We employ Bayesian variable selection approaches using a structured continuous spike-and-slab prior to identify the locations that respond to a certain stimulus. We incorporate the spatio-temporal structure through a Kronecker product of the spatial and temporal correlation matrices. We develop a highly scalable estimation algorithm, using likelihood approximation, to deal with large number of parameters in the model. Variable selection is done via clustering of the locations based on their duration of activation. We use scoring rules to evaluate the prediction performance. Simulation studies demonstrate the efficiency of our scalable algorithm in terms of estimation and fast computation. We present results using our scalable approach on a case study of multi-subject EEG data. Les auteurs présentent une approche de modélisation bayésienne évolutive pour l’identification des régions du cerveau qui répondent à un certain stimulus afin de les utiliser pour classer les sujets. Ils travaillent nommément avec des données d’électroencéphalogramme (EEG) multi-sujets où une variable binaire distingue les sujets alcooliques des individus du groupe contrôle. Les covariables sont des matrices de mesures prises sur chaque sujet à différents endroits et différents moments. Les données d’EEG ont une structure complexe comportant des attributs spatiaux et temporels. Les auteurs adoptent une stratégie de type diviser pour régner et construisent des modèles locaux, à raison d’un modèle pour chaque point temporel. Ils mettent de l’avant une approche bayésienne de sélection de variables exploitant une loi a priori continue en pic et plateau afin d’identifier la localisation d’un certain stimulus. Ils incorporent la structure spatio-temporelle à l’aide d’un produit de Kronecker des matrices de corrélation spatiales et temporelles. Ils développent un algorithme d’estimation hautement évolutif misant sur une approximation de la vraisemblance afin de gérer le grand nombre de paramètres dans le modèle. Une sélection de variables est faite en regroupant les lieux selon la durée de leur activation. Les auteurs exploitent des règles de pointage afin d’évaluer la performance en termes de prévisions. Ils démontrent par des études de simulation l’efficacité de leur algorithme évolutif et en termes d’estimation et de rapidité des calculs. Ils présentent les résultats obtenus avec leur méthode évolutive pour une étude de cas avec des données EEG multi-sujets.